Stacey's movie - Martin, Ann M., 1955- (New York : Scholastic, 1999)
When Stacey makes a movie, she uncovers secrets that threaten her friendships.
"An Apple paperback.".
4.7
3-6
Keywords: Baby-sitting -- Fiction; Friendship -- Fiction; Motion pictures -- Production and direction -- Fiction; Baby-sitting -- Fiction; Friendship -- Fiction; Motion pictures -- Production and direction -- Fiction